SLOPE SCALE VARIATION OF FLOW PATTERNS IN SOIL PROFILES - Zehe E.; Fluhler H. (My University, 2001)
Tracer patterns in soil profiles observed in ten transport experiments using a dye and Bromide are analysed to investigate the spatial distribution of the susceptibility for preferential flow on the slope scale. Flow patterns are characterised by interval scaled parameters that describe the plot scale variation of the vertical transport. This measure is used for a cluster analysis to discriminate similar flow patterns. A discriminant analysis of the obtained clusters shows whether the membership of a flow pattern to a cluster may be explained by independent quantities that characterise the conditions of the corresponding transport experiment and relative position of the field site on the slope. The results suggest that sites located at the bottom of the slopes, especially sites that are located near the brook, have a higher susceptibility for preferential flow than those in the upper parts of a hill. This is a characteristics of soil formation of hill slope soil catenas, which usually leads to deeper, biologically more active, and often, finer textured soils in the hill foot sector. This in turn strongly affects the transport regime of these soils.
Keywords: PREFERENTIAL FLOW; SCALING; PATTERN; STATISTICAL ANALYSIS; EXPERIMENTS